Investigating the Effectiveness of Utilizing the Online Teaching via Flipped Learning Procedures for Improving the Undergraduates’ English Communicative Skills - Patcharin Kangkha; Jittima Choopun; Boonyarit Omanee; Suchada Buntho (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This research study aimed at investigating the effectiveness of online teaching via flipped learning procedures for improving the undergraduates’ English communicative skills (listening and speaking, reading and writing, grammar and vocabulary, and communicative flow ability). The participants were 186 undergraduates from the Faculty of Engineering including 41 Electronic Engineering students, and 48 Civil Engineering students; and Faculty of Business Administration including 49 General Administrative students and 48 Accounting students who had enrolled the English for Everyday Use course in the academic year 2020 at Faculty of Liberal class, Rajamanagala University of Technology Srivijaya Songkhla. The research instruments were a pretest and a posttest for the participants’ achievements of the online flipping the classrooms and a semi-structured interview was conducted to draw a clear picture of the online teaching via flipped learning procedures. The major findings of the study revealed that there were significant differences in English communicative skills and areas among four groups. The participants from General Administrative students achieved higher scores than those three groups. The most prominent improved skills are listening and speaking, grammar and vocabulary and communication flow skills. The noticeable suggestions of the participants were highlighted for further study.